(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research dealt with the study of labor productivity in the public sector for the food and tobacco industries and the role of spending on capital equipment (investment spending) in increasing this productivity, by studying labor productivity and actual spending on capital equipment items (lands, buildings and construction, machinery and equipment, means of transportation, tools, furniture and office equipment, expenses of establishment and test runs). This research studied the concept of productivity and its importance of the national economy, and its importance for both workers, employers, investors, and consumers, were discussed. The elements of productivity, such as capital equipment, land and raw materials, and manpower, and the way they affect productivity in general. Then we discussed labor productivity, its definition and importance, and studied the impact of spending on capital equipment items (investment spending) on ​​labor productivity, by studying production in the studied sector during the study period (2010-2019) and the accompanying change in the number of workers and the productivity of one worker. And the study of investment spending that was actually made on the items of investment spending (according to the Central Bureau of Statistics data) and then studying the link between it and labor productivity in order to know its impact on work productivity, and it was concluded that there is no impact of spending on machinery, lands and operating experiments on labor productivity. And the existence of a role for spending on buildings and constructions, transportation, tools, and furniture on labor productivity.